Association between extramarital sexual activity, number of sexual partners, and HIV incidence among productive-age adults at H. Adam Malik general hospital, Medan - Erwina, Bella Putri; Ismah, Zata (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2024)
HIV/AIDS remains a critical global health challenge, characterized by significant morbidity and mortality. In 2022, Medan reported 1,543 HIV/AIDS cases, with the majority occurring in individuals aged 15–64 years. This study investigates the associations between extramarital sexual activity, the number of sexual partners, and the incidence of HIV among productive-age adults treated at H. Adam Malik General Hospital, Medan, Indonesia. An analytical observational case-control study was employed with 108 participants (54 cases and 54 controls). The analysis identified significant associations between extramarital sexual activities, the number of sexual partners, and HIV infection risk. These findings highlight the urgent need for strengthened global initiatives such as the "Getting to Zero" campaign, youth empowerment through NGOs, and enhanced public health education. Collaborative efforts involving the healthcare sector and government agencies are critical to improving HIV prevention strategies and reducing transmission rates.